High risk device registries: Global value, costs, and sustainable funding. Issue 9 (September 2018) - Becherer, Babette E.; Spronk, Pauline E.R.; Mureau, Marc A.M.; Mulgrew, Stephen; Perks, A Graeme B.; Stark, Birgit; Pusic, Andrea L.; Lumenta, David B.; Hopper, Ingrid; Cooter, Rodney D.; Rakhorst, Hinne A.
Summary: Background: Well-designed implant registries have been shown to be a worthwhile investment, from both a health and economic perspective. However, many registries do not attain desirable capture rates or lack sufficient funding, potentially leading to premature termination. This study aims to provide information about rarely discussed, yet pivotal topics regarding the long-term survival of implant registries, focusing on costs, funding models, and the role of stakeholders. Methods: Worldwide, relatively recently developed breast device (BD) registries were compared to long-standing, orthopaedic (OD) and cardiovascular device (CD) registries. A standardised questionnaire was sent to the registries' designated representatives with key positions, discussing start-up costs, costs of maintenance, value of investment, governance, stakeholders, funding, and sustainability. Results: Thirteen registries were included, originating from nine countries (seven BD registries, five OD registries, one CD registry). In general, start-up costs were comparable, and younger registries were more expensive to maintain. Numerous stakeholders showed interest in registry outcomes. However, only 50% of the registries reported a sustainable funding structure. Conclusion: This study provides a global perspective on implantable device registries. All registries provided important information, serving three unique purposes by evaluating the quality of healthcare provided, the quality of all registered devices, and processing recall information. Yet, only half of the registries were certain of sustainable funding, and thus their future existence. It is of utmost importance to bring this to the attention of all parties involved.